Valuing a translingual mindset in researcher education in Anglophone higher education: supervision perspectives. Issue 2 (2nd April 2020) - Andrews, Jane; Fay, Richard
ABSTRACT: This article explores some implications of plurilingualism and translingual practice for teaching and learning in higher education. Research in this area tends to focus on the undergraduate experience whereas our focus is on doctoral supervision, a less-discussed but rich site for studying plurilingual and translingual practice. We consider linguistic aspects of research supervision interactions and linguistic practices in research sites in real world contexts. Revisiting a data set of written, self-reported, researcher profiles, the article explores how doctoral researchers and supervisors explain, and reflect on, their linguistic practices in supervision interactions and associated research practices. The data set is analysed by means of a thematic analysis informed by our reading of applied linguistics research into plurilingualism and translingual practice. The analysis highlights a wide range of linguistic practices and conceptualisations of languages in research, including, on the one hand, a separation of languages, and, on the other, a fluidity in how researchers use their diverse linguistic resources for different purposes in their research practice. The article concludes with the recommendation that researcher education should foreground language more than is currently evident in some Anglophone higher education contexts, and that this can be framed in terms of plurilingualism and translingual practice.